Effect of Managerial Overconfidence on Ranking of Financing Decisions by Financial Managers of Firms Listed In NSE - Nyakundi, Judith; Njuguna, Prof. Amos; Omboi, Dr. Bernard (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to determine the effect of overconfidence on ranking of financing decisions by financial managers of firms listed in NSE. Methodology: The study employed a positivism philosophy and a descriptive correlational design. A two tier sampling was applied where; a census at the firm level and purposive sampling at financial manager level resulting with a selection of the top 3 senior and middle financial managers from each firm. The target population was the top three financial managers in each of the firms listed in the NSE resulting in a target population of 192 financial managers from a population of 64 firms. A questionnaire was utilised to collect primary data from the target population. Descriptive statistics, Analysis of Variance (ANOVA) and multinomial logit regression were employed in data analysis. Results: Findings depict a significant effect of overconfidence on ranking of financing decisions by managers in firms listed in NSE. Managers who were predisposed to overconfidence bias were more inclined towards debt and equity compared to internal capital, with equity most preferred followed by debt then internal sources of capital. Unique Contribution to Theory Practice and policy: Consequently, it is recommended that the implications of overconfidence be considered by financial managers to constantly refine financing techniques. This will help handle the new set of challenges that come with need to strike a value adding balance on financing decisions.